La Teichoskopia en Fenicias de Eurípides. La guerra vistas desde las murallas - María del Carmen Encinas Reguero (Talia dixit)
Euripides’ Phoenician Women includes a teichoskopia in which the dramatist partially reworked the shield scene in Aeschylus’ Seven Against Thebes.. Analyzing the teichoskopia in light of the Aeschylean scene allows one not only to understand its function in the play, a function even now still open to interpretation, but also to perceive how Euripides saw the war